IoT implementation in systems spraying pheromones pineapple skin for control integrated bee horn coconut palm oil - Irvana Dima Saputra; Shabri Putra Wirman; Neneng Fitria; Diana Putrianti (Universitas Sebelas Maret, 2026)
This study presents the design and evaluation of an Internet of Things (IoT)-based automated pheromone spraying system for the control of Oryctes rhinoceros in oil palm plantations. The proposed system integrates a microcontroller with an infrared sensor, a load cell, a real-time clock (RTC), a GSM communication module, and an ultrasonic mist generator to support real-time monitoring and automated pheromone release. Experimental procedures included component validation and field testing conducted over a seven-day period. The results demonstrate that the infrared sensor achieved a detection accuracy of 100% under low-light conditions, while the load cell showed a coefficient of variation of approximately 2%, indicating high measurement precision. The GSM module was capable of transmitting data with delays ranging from 0 to 51 seconds over a communication range of up to 5 km. Field evaluation further revealed that the trap positioned at a height of 2.5 meters yielded the highest capture rate of rhinoceros beetles compared to other configurations. Overall, the findings indicate that the developed system is reliable, energy-efficient, and applicable for sustainable pest management in oil palm plantations.